Numerical Study on the Flow and Heat Transfer Coupled in a Rectangular Mini-Channel by Finite Element Method for Industrial Micro-Cooling Technologies - Claude Aurélien Kamdem Kamdem; Xiaolu Zhu (Fluids, 2020)
Nowadays, cooling high thermal flows in compact volumes continues to be one of the crucial problems in the industry. With the advent of advanced technologies, much more attention has been paid to how to improve the performance of cooling systems in the area of micro-technologies. Rectangular mini-channels are typical representatives which commonly used for cooling applications. However, micro-technologies still face the problem of low performance due to the low productivity of cooling related to unbefitting physical parameter values. Here, this work studies the applicability of the heat transfer scheme of convective flow and flow boiling in a rectangular mini-channel for satisfying the cooling requirement of industrial micro-technologies, through a simulation model governed by the coupled mechanism from Navier-Stokes (N-S) equation and heat transfer equations with phase change effect. In this work, various hydraulic diameters and different inlet fluid speed are used to calculate the different velocity profiles, pressure drops, coefficients of friction and finally, the distribution of the temperatures and dissipated heat flux. The simulation results show the applicability of the rectangular mini-channel in diverse applications such as engine cooling, electronic components, automotive on-board electronics and aerospace engineering. Flow boiling simulation results reveal that the obtained patterns were smooth mixture flow and discrete flow. The dissipated heat flux can reach 1.02–5.34 MW/m2 for a hydraulic diameter of 0.5 mm. We show that the system with the gradient temperature that evolves increasingly along the top and bottom walls of the channels presents the highest heat flux dissipated in flow boiling. Additionally, the fin efficiency of the system is 0.88 and the coefficient value of convective heat transfer is in the range between 5000 < h < 100,000, which indicates the flow boiling heat transfer is effective in the mini-channel when the Reynolds number is less than 400. It provides a significant heat exchange for cooling in these application areas.